Geometrically constrained particle dynamics revisited: Equation of motion in terms of the normal curvature of the constraint manifold - Hsiao, Wei-Han (2024)
We revisit the problem of the particle dynamics subject to a geometric holonomic constraint of codimension 1 in spatial dimensions d =2 and 3. In the absence of dissipation, we show that by solving the Lagrangian multiplier in a general fashion, the external potential independent part, the net normal force, of the equation of motion corresponds to precisely to the curvature of the trajectory on the constraint space multiplied by twice the kinetic energy. The tangent the trajectory is the instantaneous velocity. In d = 3, this term equals the second fundamental form II of the constraint surface evaluated on the unit tangent vector in the direction of velocity. Using these result we establish the relation between constrained particle dynamics with geodesic equations and derive intriguing kinematic implications using theorems from fundamental differential geometry.